2014
DOI: 10.1177/1094428114525996
|View full text |Cite
|
Sign up to set email alerts
|

General Mental Ability as a Source of Differential Functioning in Personality Scales

Abstract: Despite pervasive evidence that general mental ability and personality are unrelated, we investigated whether general mental ability may affect the response process associated with personality measurement. Study 1 examined a large sample of job applicant responses to four personality scales for differential functioning across groups of differing general mental ability. While results indicated that personality items differentially function across highly disparate general mental ability groups, there was little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…This study adds to the current literature by measuring cognitive ability both directly and indirectly. Until now, the differentiation of personality by the cognitive ability hypothesis was under-analyzed in high-stakes contexts, such as job selection processes ( DuVernet et al 2014 ; McLarnon and Carswell 2013 ; Schermer et al 2020b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study adds to the current literature by measuring cognitive ability both directly and indirectly. Until now, the differentiation of personality by the cognitive ability hypothesis was under-analyzed in high-stakes contexts, such as job selection processes ( DuVernet et al 2014 ; McLarnon and Carswell 2013 ; Schermer et al 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, practitioners who use personality instruments in selection contexts should be aware of the potential limitations and biases that may arise from using a one-size-fits-all approach. Alternatively, they could use more adaptive and flexible personality measures that can adjust to individual differences in personality structure, such as CAT (computerized adaptive testing)- or IRT (item response theory)-based instruments ( DuVernet et al 2014 ; McLarnon and Carswell 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Possibly the managers who were more intelligent in this sample responded consistently to the agreeableness items as they perceived agreeableness as an attractive dimension for their careers. How the differentiation of personality by intelligence hypothesis behaves in high stakes situations, such as job selection situations are under analyzed and less understood (DuVernet et al, 2014;McLarnon & Carswell, 2013;Schermer et al, 2020bSchermer et al, , 2020c.…”
Section: Discussionmentioning
confidence: 99%
“…DuVernet et al's (2014) investigation of the differentiation hypothesis included four facets: empathy, optimism, emotional control, and responsibility. In their study, DuVernet et al (2014) reported that the psychometric properties of personality items changed by mental ability and the authors suggested that mental ability may impact how people process personality items. Shure and Rogers (1963) reported that the factor structure of the California Psychological Inventory scales differed for individuals who differed in terms of intelligence but not the number of factors.…”
Section: Introductionmentioning
confidence: 99%